2017
DOI: 10.1364/oe.25.026950
|View full text |Cite
|
Sign up to set email alerts
|

Dual Kretschmann and Otto configuration fiber surface plasmon resonance biosensor

Abstract: We present a dual-resonance fiber surface plasmon resonance (SPR) sensor for biological analysis. The sensing element was fabricated by sequentially sputtering layers of indium tin oxide (ITO) (100 nm thickness) and Au (35 nm thickness) on the surface of an optical fiber. The refractive index dispersion effect of ITO material led to resonances in the near infrared and visible wavelength regions. The refractive index of ITO is larger than the optical fiber in visible spectral area (400 to 733nm), such that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 23 publications
1
24
0
1
Order By: Relevance
“…It is important to appreciate that the interaction volume plays an important role in plasmonic sensor characteristics. Some of the research works based on fiber-optic SPR sensors have also demonstrated the field distribution along the analyte side under resonance conditions [40,41]. The field enhancement towards the analyte region increases the interaction volume.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to appreciate that the interaction volume plays an important role in plasmonic sensor characteristics. Some of the research works based on fiber-optic SPR sensors have also demonstrated the field distribution along the analyte side under resonance conditions [40,41]. The field enhancement towards the analyte region increases the interaction volume.…”
Section: Resultsmentioning
confidence: 99%
“…It illustrates that the normalized intensity shift as a function of RI can be linear fitted in the RI range of 1.326 to 1.351, which can be used for many biochemical samples measurement. 25,26 In the RI range of 1.326 to 1.351, the system provides a sensitivity of 11.542/RIU. Analysis of the baseline noise was also performed.…”
Section: Red-green Dual-color Fiber Optic Spr Sensormentioning
confidence: 99%
“…Такой резонанс можно использовать как опорный при сравнении с изменением положения резонанса по Кретчману, что позволит повысить точность и стабильность работы двухрезонансной структуры в режиме сенсора по сравнению с однорезонансной. Отметим, что другими исследовательскими группами также предпринимаются подобные шаги по созданию двухрезонансных плазмонных систем, совмещающих резонансы Отто и Кретчмана, например, на спектральных датчиках оптоволоконного типа с буферным слоем, имеющим сильную дисперсию диэлектрической проницаемости [11].…”
Section: Introductionunclassified